Interaction in distance education and online learning: using evidence and theory to improve practice - Abrami, Philip C.; Bernard, Robert M.; Bures, Eva M.; Borokhovski, Eugene; Tamim, Rana M. (Journal of computing in higher education, 2011)
In a recent meta-analysis of distance and online learning, Bernard et al. ( 2009 ) quantitatively verified the importance of three types of interaction: among students, between the instructor and students, and between students and course content. In this paper we explore these findings further, discuss methodological issues in research and suggest how these results may foster instructional improvement. We highlight several evidence-based approaches that may be useful in the next generation of distance and online learning. These include principles and applications stemming from the theories of self-regulation and multimedia learning, research-based motivational principles and collaborative learning principles. We also discuss the pedagogical challenges inherent in distance and online learning that need to be considered in instructional design and software development.